2020
DOI: 10.1186/s12883-020-01710-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of spinal dysraphism with a hamartomatous growth (appendix) of the spinal cord: a case series

Abstract: Background: Spinal dysraphism with a hamartomatous growth (appendix) of the spinal cord is better known as herniated spinal cord. There are many arguments in favour of considering it a developmental defect. From this point of view, it is a type of neural tube disorder. Neural tube disorders can be caused by multiple factors, including a genetic factor. A common genetic defect in patients with a spinal dysraphism with a hamartomatous growth of the spinal cord is sought for. Case presentation: In two patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…However, study of disease involved tissue may be critical, in addition to use of sensitive methods to resolve low frequency and/or structurally complex variation. Recently, exome sequencing of genomic DNA from two individuals with SD and hamartomatous lesions was not revealing for an underlying genomic event (Bartels et al 2020). Limiting sample size (n=2), and the tissue under study may have been contributory to the inability to establish a genetic association with disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, study of disease involved tissue may be critical, in addition to use of sensitive methods to resolve low frequency and/or structurally complex variation. Recently, exome sequencing of genomic DNA from two individuals with SD and hamartomatous lesions was not revealing for an underlying genomic event (Bartels et al 2020). Limiting sample size (n=2), and the tissue under study may have been contributory to the inability to establish a genetic association with disease.…”
Section: Discussionmentioning
confidence: 99%
“…During review of the previously reported literature, only three documented cases were found having no features of such association [1,9,10] . Beside this, there is no genetic predisposition found for this hamartomatous lesion [14] .…”
Section: Associated Anomaliesmentioning
confidence: 93%